2003
DOI: 10.1128/iai.71.12.7154-7158.2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Salmonella enterica Serovar Typhimurium Biofilm Formation on Gallstones and on Glass

Abstract: In this study, the roles of global regulators, motility, lipopolysaccharide, and exopolysaccharides were further characterized with respect to biofilm formation on both gallstones and glass surfaces. These studies show the complex nature of biofilms and demonstrate that characteristics observed for each biofilm are unique to the particular culture condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 35 publications
8
133
0
1
Order By: Relevance
“…LPS-defective mutants of Salmonella enterica and Pseudomonas fluorescens have been shown to differ from their parental strains in their ability to adhere to inert surfaces (Williams & Fletcher, 1996;Prouty & Gunn, 2003). Here, while the noeJ mutant was able to adhere to and form biofilm on glass similarly to the wild-type, the noeL mutant was defective in its biofilm formation ability on glass.…”
Section: Discussionmentioning
confidence: 99%
“…LPS-defective mutants of Salmonella enterica and Pseudomonas fluorescens have been shown to differ from their parental strains in their ability to adhere to inert surfaces (Williams & Fletcher, 1996;Prouty & Gunn, 2003). Here, while the noeJ mutant was able to adhere to and form biofilm on glass similarly to the wild-type, the noeL mutant was defective in its biofilm formation ability on glass.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the many bacterial factors that have been implicated, the biophysical properties of the substrate and surrounding medium can also greatly influence bacterial biofilm formation (Heydorn et al 2000;Prouty and Gunn 2003). For example, C. elegans mutants with an altered surface cuticle do not accumulate Yersinia biofilm (Höflich et al 2004;Joshua et al 2003).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In a number of experimental studies, the ability of Salmonella to form BF on a variety of materials such as concrete, glass (Prouty and Gunn, 2003), cement (Joseph et al, 2001), stainless steel (Oliveira et al, 2007), plastic (Stepanović et al, 2004;Solomon et al, 2005), granite and rubber (Arnold and Yates, 2009) was confirmed (Solano et al, 2002;Steenackers et al, 2012). Salmonella spp.…”
Section: B I O F I L M F O R M I N G C a Pa C I T Y O F Salmonella Spmentioning
confidence: 99%